New Concepts of Kazakh Literature Periodization - Sagymbay Zhumagulov (Evropejskij Issledovatelʹ, 2013)
The article attempts to reconsider Kazakh literature periodization from today’s perspective. The researchers define the value of scientific investigation in terms of literary trends and directions, applied in the history of the Kazakh literature and reconsideration of the facts and concepts distorted by ideology. The main goal of the article is to research and study scientific and literary heritage of ingenious literary artists and public figures, whose oeuvres belong to different historical periods of the Kazakh literature, reintroduce their valuable works for scientific use. Prospects of scientific investigations on the basis of the research methodology and the advanced scientific principles are determined